Policy enablers and perceived impediments of rooftop solar photovoltaic projects in Gauteng, South Africa - Munemo, Pride Takudzwa (University of the Witwatersrand, Johannesburg, 2024)
The issue of climate change has necessitated that many countries shift to greener and more sustainable energy sources. South Africa’s plans to encourage the generation of power from solar energy is a positive move in decarbonising the country’s economy. The National Integrated Resource Plan (IRP) intends to, among others, contribute to this shift and transition in power generation technologies. Despite being one of the two provinces in South Africa with the highest solar PV potential that may aid the penetration of rooftop solar PV (RSPV), the Gauteng province’s roll-out of such projects is perceived to be slower than anticipated. This research sought to study the perceived impediments that are hindering the growth of RSPV in the Gauteng province, reveal their impact in this sector, and explore the enablers for the diffusion of RSPV evolution. The Diffusion of Innovation theory forms the foundation for this study. The research investigated perceived policy impediments and enablers and suggested some policy measures to address these cross-cutting issues and contribute to the academic body of knowledge. The research approach was quantitative, and descriptive in nature, and information was obtained using a questionnaire that was administered via Survey Monkey. Data was gathered by integrating perspectives from key rooftop solar industry experts from energy service companies and regulatory sector officials. The study administered questions to participants in key energy leadership positions in the rooftop solar industry in the Gauteng province to understand perceived barriers and policy enablers. This research paper may assist academics, energy practitioners, and regulators in focusing their future efforts on the adoption of rooftop solar technologies in the Gauteng province. Furthermore, it may help in developing a framework for policies and strategies to increase the uptake of rooftop solar in South Africa.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Energy Leadership to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Impediments; Enablers; Rooftop Solar; PV Uptake; Diffusion; Policy; Gauteng Province; UCTD; SDG-9: Industry, innovation and infrastructure